Polarizing membranes and films

A polarizing film with high iodine content and a peak water detection temperature of 175°C stabilizes against coloration in high-temperature environments, ensuring low single transmittance and high polarization.

JP7609565B2Active Publication Date: 2025-01-07NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020072070
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-14
Publication Date
2025-01-07
Estimated Expiration
2040-04-14

AI Technical Summary

Technical Problem

Conventional thin polarizing films do not sufficiently suppress the decrease in single transmittance in high-temperature environments, and there is a trade-off between high iodine content for high polarization and maintaining transmittance.

Method used

A polarizing film with an iodine content of more than 10% by weight, a single transmittance of 41% or less, and a peak temperature of water detection in evolved gas analysis at 175°C or higher, optionally containing a radical scavenger to stabilize the film in high-temperature conditions.

Benefits of technology

The film effectively maintains low single transmittance and high polarization by delaying the dehydration reaction of polyvinyl alcohol, thereby suppressing coloration and maintaining optical performance in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609565000011
    Figure 0007609565000011
  • Figure 0007609565000001
    Figure 0007609565000001
  • Figure 0007609565000002
    Figure 0007609565000002
Patent Text Reader

Abstract

To provide a polarization membrane containing much iodine, in which an initial single body transmission is 41% or less and the transmission is prevented from becoming smaller due to coloring of the polarization membrane under a high-temperature environment.SOLUTION: There is provided a polarization film formed in such a manner that iodine is adsorbed and oriented to a polyvinyl alcohol film. The content of iodine is larger than 10% by weight, the single body transmission is 41% or smaller, and the peak temperature when detected water has the largest intensity is at least 175°C under the condition in which there is an inactive gas, the rate of rise of the temperature is 10°C / minute, the range of rise of the temperature is 40°C-350°C in a gas generation analysis.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing membrane and a polarizing film. [Background technology]

[0002] Conventionally, a dyed polyvinyl alcohol film (containing a dichroic substance such as iodine or a dichroic dye) has been used as a polarizing film for use in various image display devices such as liquid crystal display devices and organic EL display devices, because it has both high transmittance and high polarization degree. The polarizing film is produced by subjecting a polyvinyl alcohol film to various treatments such as swelling, dyeing, crosslinking, and stretching in a bath, followed by washing and drying. The polarizing film is usually used as a polarizing film (polarizing plate) with a protective film such as triacetyl cellulose attached to one or both sides of the polarizing film using an adhesive.

[0003] On the other hand, as polarizing films become thinner, polarizing films with a higher iodine content are in demand (Patent Document 1).Furthermore, even for such thin polarizing films, there are known ones that can suppress the amount of change in single-unit transmittance in a high-temperature environment (105°C x 30 hours) (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 186244 [Patent Document 2] International Publication No. 2019 / 103002 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the thin polarizing films specifically disclosed in Patent Documents 1 and 2 do not sufficiently suppress the decrease in single-unit transmittance in a high-temperature environment, and there is room for improvement in this performance.

[0006] On the other hand, the present inventors have found that iodine contained in an iodine-based polarizing film promotes polyenation in a high-temperature environment. Therefore, in order to suppress the decrease in the single-unit transmittance due to coloring of the polarizing film in a high-temperature environment, it is effective to reduce the iodine content in the polarizing film. On the other hand, it has been difficult to obtain a polarizing film with a high iodine content and a good polarization degree.

[0007] Furthermore, as described in Patent Document 2, in polarizing films with a high iodine content, a polarizing film with a single transmittance of 41% or less is required, from the viewpoint that contrast can be increased by setting the single transmittance low.

[0008] In view of the above circumstances, an object of the present invention is to provide a polarizing film having a high iodine content, which has an initial single-unit transmittance of 41% or less and is excellent in preventing a decrease in the single-unit transmittance due to coloring of the polarizing film in a high-temperature environment.

[0009] Another object of the present invention is to provide a polarizing film using the above polarizing membrane. [Means for solving the problem]

[0010] That is, the present invention relates to a polarizing film formed by adsorbing and orienting iodine on a polyvinyl alcohol-based film, the polarizing film having an iodine content of more than 10% by weight, a single-unit transmittance of 41% or less, and a peak temperature of the maximum intensity of detected water of 175°C or higher in evolved gas analysis under conditions of a heating rate of 10°C / min in the presence of an inert gas and a heating range of 40°C to 350°C.

[0011] The present invention also relates to a polarizing film in which a transparent protective film or an optically functional film is laminated to at least one surface of the polarizing film. Effect of the Invention

[0012] Although the details of the mechanism of action of the polarizing film of the present invention are unclear, it is presumed as follows: However, the present invention is not necessarily limited to this mechanism of action.

[0013] The polarizing film of the present invention is a polarizing film formed by adsorbing and orienting iodine on a polyvinyl alcohol-based film, the iodine content is more than 10% by weight, the single-unit transmittance is 41% or less, and the peak temperature of the maximum water intensity detected in evolved gas analysis is 175° C. or more in the presence of an inert gas, at a temperature rise rate of 10° C. / min, and in a temperature rise range of 40° C. to 350° C. As described above, in an iodine-based polarizing film, polyenization occurs due to a dehydration reaction of polyvinyl alcohol in a high-temperature environment, but the polarizing film of the present invention can suppress a decrease in the single-unit transmittance caused by coloring of the polarizing film in a high-temperature environment by setting the temperature at which this dehydration reaction occurs on the high-temperature side, i.e., by setting the peak temperature of the maximum water intensity detected (observed) by evolved gas analysis to 175° C. or more. Furthermore, by setting the iodine content in the polarizing film to a certain level or higher, the peak temperature of the maximum water intensity detected (observed) by evolved gas analysis can be controlled to 175°C or higher, while the single-unit transmittance is 41% or lower and the initial polarization degree is good.

[0014] Meanwhile, the present inventors have observed the generation of radicals from a polarizing film formed by adsorbing and orienting iodine on an iodine-containing polyvinyl alcohol film when the film is exposed to a high-temperature environment for a certain period of time. The timing at which the polarizing film becomes colored due to polyenation and the timing at which the radicals are generated are very similar, suggesting the phenomenon that radicals are generated due to the progress of polyenation of the polarizing film. Therefore, in order to set the temperature at which the above-mentioned dehydration reaction occurs in the polarizing film to a high temperature side, that is, to set the peak temperature of the maximum water intensity detected (observed) by evolved gas analysis to 175°C or higher, it is preferable to include a radical scavenger in the polarizing film. [Brief description of the drawings]

[0015] [Figure 1]1 is an example of a chart showing a water peak detected in an evolved gas analysis method using an iodine-based polarizing film as a sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Polarizing film> The polarizing film of the present invention is an iodine-based polarizing film formed by adsorbing and orienting iodine on a polyvinyl alcohol-based film, and has an iodine content of more than 10% by weight, a single-piece transmittance of 41% or less, and a peak temperature of the maximum intensity of detected water of 175°C or more in the presence of an inert gas, at a heating rate of 10°C / min, and in a heating range of 40°C to 350°C, as measured by evolved gas analysis.

[0017] The polarizing film has an iodine content of more than 10% by weight from the viewpoint of improving the initial polarization degree of the polarizing film. The polarizing film has an iodine content of preferably 12% by weight or more, more preferably 15% by weight or more, from the viewpoint of controlling the initial polarization degree to 99.98 or more, and the polarizing film has an iodine content of preferably 30% by weight or less, more preferably 25% by weight or less, from the viewpoint of controlling the peak temperature of the maximum intensity of water detected by evolved gas analysis to 175° C. or more.

[0018] From the viewpoint of controlling the initial polarization degree to 99.98 or more, the polarizing film preferably has a thickness of 0.2 μm or more, and more preferably 0.5 μm or more, and from the viewpoint of reducing the thickness of the polarizing film, the thickness is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 5 μm or less.

[0019] The polarizing film has a single transmittance of 41% or less. From the viewpoint of display panel luminance, the polarizing film has a single transmittance of preferably 30% or more, more preferably 35% or more, and from the viewpoint of controlling the initial polarization degree to 99.98 or more, the single transmittance is preferably 41% or less, more preferably 40% or less. The single transmittance is a Y value measured using an integrating sphere spectrophotometer (for example, product name: V7100 manufactured by JASCO Corporation) with a 2-degree visual field (C light source) according to JIS Z8701 and corrected for luminous efficiency.

[0020] The polarizing film exhibits a peak temperature of maximum water intensity of 175°C or more in the presence of an inert gas, at a temperature rise rate of 10°C / min, and in a temperature range of 40°C to 350°C, in an evolved gas analysis. The polarizing film can suppress a decrease in single-unit transmittance due to coloring of the polarizing film in a high-temperature environment by setting the temperature at which a dehydration reaction of polyvinyl alcohol occurs on the high-temperature side, i.e., by setting the peak temperature of maximum water intensity detected by evolved gas analysis to 175°C or more. On the other hand, if the peak temperature of maximum water intensity is lower than 175°C or more, it becomes difficult to control the change in single-unit transmittance of the polarizing film before and after a heating durability test (105°C x 96 hours), which is used as an index of the heat resistance of a display, to 0% or more and 5% or less.

[0021] FIG. 1 is an example of a chart showing the peaks of water detected by the evolved gas analysis method described above, and the peak temperature of the maximum intensity of detected water is 175° C. or higher.

[0022] The evolved gas analysis method is an analytical method in which a gas chromatograph and a mass spectrometer are directly connected using an inert metal capillary or the like, and the gas evolved when the sample is heated is monitored in real time; this method is generally called the EGA / MS method or the EGA / TOFMS method.

[0023] The polarizing film preferably contains a radical scavenger. It is presumed that the radical scavenger can capture radicals generated by the heating of the polyvinyl alcohol of the polarizing film, and can set the temperature at which the dehydration reaction of polyenization occurs to a high temperature. Examples of the radical scavenger include radical scavengers such as hindered phenol-based, hindered amine-based, phosphorus-based, sulfur-based, benzotriazole-based, benzophenone-based, hydroxylamine-based, salicylic acid ester-based, and triazine-based compounds. The radical scavenger is preferably, for example, a compound having a nitroxy radical or a nitroxide group, from the viewpoint of easily setting the temperature at which the dehydration reaction of polyenization occurs to a high temperature.

[0024] As the nitroxy radical or the compound having a nitroxide group, from the viewpoint of having a radical that is relatively stable in air at room temperature, an N-oxyl compound (having a functional group of CN(-C)-O · Compounds having the formula (O · The N-oxyl compound may be, for example, a compound having an organic group of the following structure: [ka] (In general formula (1), R 1 represents an oxy radical, and R 2 From R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n represents 0 or 1.) In addition, in general formula (1), the left of the dotted line represents any organic group.

[0025] Examples of the compound having the above organic group include compounds represented by the following general formulas (2) to (5). [ka] (In general formula (2), R 1 ~R 5 , and n are the same as above, and R 6represents a hydrogen atom, or an alkyl group, acyl group, or aryl group having 1 to 10 carbon atoms, and n represents 0 or 1. [ka] (In general formula (3), R 1 From R 5 , and n are the same as above, and R 7 and R 8 each independently represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms. [ka] (In general formula (4), R 1 From R 5 , and n are the same as above, and R 9 From R 11 each independently represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an acyl group, an amino group, an alkoxy group, a hydroxyl group, or an aryl group. [ka] (In general formula (5), R 1 From R 5 , and n are the same as above, and R 12 represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an amino group, an alkoxy group, a hydroxyl group, or an aryl group.

[0026] In the general formulas (1) to (5), R 2 From R 5 From the viewpoint of availability, R is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. 6 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 7 and R 8are preferably independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 9 From R 11 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. 12 is preferably a hydroxy group, an amino group, or an alkoxy group. In the general formulas (1) to (5), n is preferably 1 from the viewpoint of availability.

[0027] Examples of the N-oxyl compound include the N-oxyl compounds described in JP-A-2003-64022, JP-A-11-222462, JP-A-2002-284737, and WO 2016 / 047655.

[0028] From the viewpoint of being able to efficiently capture radicals generated in the polyenation reaction, the radical scavenger preferably has a molecular weight of 1,000 or less, more preferably 500 or less, and even more preferably 300 or less.

[0029] From the viewpoints of being able to efficiently permeate into the polarizing film together with water during production of the polarizing film, being able to be impregnated into the polarizing film at a high concentration, and being able to be impregnated into the polarizing film in a short time even when a thick polyvinyl alcohol-based film is used, thereby increasing the productivity of the polarizing film, the radical scavenger is preferably able to dissolve in an amount of 1 part by weight or more in 100 parts by weight of water at 25° C., more preferably 2 parts by weight or more in 100 parts by weight of water at 25° C., and even more preferably 5 parts by weight or more in 100 parts by weight of water at 25° C.

[0030] Examples of the compound having a nitroxy radical or a nitroxide group include the following compounds: [ka] (In the general formula (6), R represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms.) [ka] [ka]

[0031] When the polarizing film contains the radical scavenger, the content of the radical scavenger in the polarizing film is preferably 0.1% by weight or more, more preferably 0.2% by weight or more, and even more preferably 0.5% by weight or more, from the viewpoint of suppressing a decrease in the single-unit transmittance due to coloration of the polarizing film in a high-temperature environment, and from the viewpoint of appearance, the content of the radical scavenger is preferably 30% by weight or less, more preferably 20% by weight or less, and even more preferably 10% by weight or less.

[0032] In addition, when the polarizing film contains the radical scavenger, the weight ratio of the content of the radical scavenger to the content of the iodine (weight ratio of the radical scavenger content / the iodine content) of the polarizing film is preferably 0.01 or more and more preferably 0.05 or more from the viewpoint of suppressing a decrease in the single-unit transmittance due to coloring of the polarizing film in a high-temperature environment, and is preferably 1.0 or less and more preferably 0.5 or less from the viewpoint of appearance.

[0033] <Method of manufacturing polarizing film> The polarizing film is produced by subjecting a polyvinyl alcohol film (PVA film) to any of a swelling step, a washing step, and a drying step, and at least a dyeing step, a crosslinking step, and a stretching step. The iodine content in the polarizing film can be controlled by the concentration of the iodine and iodides such as potassium iodide contained in any of the treatment baths in the swelling step, the dyeing step, the crosslinking step, the stretching step, and the washing step, and the treatment temperature and treatment time in each of the treatment baths. Each step may be performed in any appropriate order, and one step may be performed multiple times as necessary.

[0034] The polyvinyl alcohol-based film has translucency in the visible light region, and can be used without any particular limitation as long as it disperses and adsorbs dichroic substances such as iodine and dichroic dyes. Examples of the polyvinyl alcohol-based film include polyvinyl alcohol or its derivatives. Examples of the polyvinyl alcohol derivatives include polyvinyl formal, polyvinyl acetal, olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and those modified with alkyl esters and acrylamides thereof. The polyvinyl alcohol preferably has an average degree of polymerization of about 100 to 10,000, more preferably about 1,000 to 10,000, and even more preferably about 1,500 to 4,500. The polyvinyl alcohol preferably has a saponification degree of about 80 to 100 mol%, and more preferably about 95 mol% to 99.95 mol. The average degree of polymerization and the saponification degree can be determined in accordance with JIS K 6726.

[0035] The polyvinyl alcohol-based film may contain additives such as plasticizers and surfactants. Examples of the plasticizers include polyols such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol, and condensates thereof. The amount of the additives used is not particularly limited, but is preferably about 20% by weight or less in the polyvinyl alcohol-based film.

[0036] The polyvinyl alcohol-based film may be a laminate in which a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a polyvinyl alcohol-based resin (PVA-based resin) is formed on one side of a long thermoplastic resin substrate. Any appropriate method may be used to prepare the laminate, and an example of the method includes applying a coating liquid containing the PVA-based resin to the surface of the thermoplastic resin substrate and drying the coating liquid. The thickness of the thermoplastic resin substrate is preferably about 20 to 300 μm, and more preferably about 50 to 200 μm. The thickness of the PVA-based resin layer is preferably about 3 to 40 μm, and more preferably about 3 to 20 μm.

[0037] Any suitable thermoplastic resin may be used as the constituent material of the thermoplastic resin substrate. Examples of the thermoplastic resin include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferred, and amorphous polyethylene terephthalate resins are preferably used because the thermoplastic resin substrate has excellent stretchability and can suppress crystallization during stretching. Examples of amorphous polyethylene terephthalate resins include copolymers containing isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acids, and copolymers containing cyclohexanedimethanol or diethylene glycol as glycols.

[0038] The thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.) before forming the PVA-based resin layer, or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved. In addition, the thermoplastic resin substrate may be stretched before forming the PVA-based resin layer.

[0039] The coating liquid is a solution in which a PVA-based resin is dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine, with water being preferred. These can be used alone or in combination of two or more. The concentration of the PVA-based resin in the coating liquid is preferably about 3 to 20 parts by weight relative to 100 parts by weight of the solvent, from the viewpoint of forming a uniform coating film that is in close contact with the thermoplastic resin substrate.

[0040] The coating liquid may contain a halide from the viewpoint of improving the orientation of polyvinyl alcohol molecules by stretching. Any appropriate halide may be used as the halide, and examples of the halide include iodide and sodium chloride. Examples of the iodide include potassium iodide, sodium iodide, and lithium iodide, and potassium iodide is preferred. The concentration of the halide in the coating liquid is preferably about 5 to 20 parts by weight, and more preferably about 10 to 15 parts by weight, relative to 100 parts by weight of the PVA resin.

[0041] The coating liquid may contain additives, such as plasticizers, such as ethylene glycol and glycerin, and surfactants, such as nonionic surfactants.

[0042] As a method for applying the coating liquid, any appropriate method can be adopted, and examples thereof include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (such as comma coating).

[0043] In the stretching step, the PVA-based film is typically uniaxially stretched about 3 to 7 times. The stretching direction may be the longitudinal direction (MD direction) of the film or the width direction (TD direction) of the film. From the viewpoint of laminating with a transparent protective film or an optically functional film by roll-to-roll, the stretching direction is preferably the TD direction. The stretching method may be dry stretching, wet stretching, or a combination of these. The PVA-based film may be stretched during a crosslinking step, a swelling step, a dyeing step, or the like. The stretching step may be performed in one step or multiple steps. When performed in multiple steps, the stretching ratio is the product of the stretching ratios in each step. The stretching direction may correspond to the absorption axis direction of the resulting polarizing film.

[0044] The swelling step is carried out before the dyeing step, if necessary. The swelling step is carried out, for example, by immersing the PVA-based film in a swelling bath. As the swelling bath, water such as distilled water or pure water is usually used. The swelling bath may contain any other appropriate components other than water. Examples of the other components include solvents such as alcohol, additives such as surfactants, and iodides. Examples of the iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide, and potassium iodide is preferred. The temperature of the swelling bath is, for example, about 20 to 45° C. The immersion time is, for example, about 10 to 300 seconds.

[0045] The dyeing step is a step of dyeing the PVA film with a dichroic substance. Examples of the adsorption method include a method of immersing the PVA film in a dyeing solution containing the dichroic substance, a method of applying the dyeing solution to the PVA film, and a method of spraying the dyeing solution onto the PVA film. From the viewpoint of good adsorption of the dichroic substance, the method of immersing the PVA film in the dyeing solution is preferred.

[0046] Examples of the dichroic material include iodine and dichroic dyes, and iodine is preferred. When iodine is used as the dichroic material, an iodine aqueous solution is preferably used as the dyeing solution. The iodine content of the iodine aqueous solution is preferably about 0.04 to 5.0 parts by weight relative to 100 parts by weight of water. In addition, in order to increase the solubility of iodine in water, it is preferable to mix an iodide into the iodine aqueous solution. As the iodide, potassium iodide is preferably used. The iodide content is preferably about 0.3 to 15 parts by weight relative to 100 parts by weight of water. From the viewpoint of obtaining a polarizing film having good optical properties, the ratio of the iodine and iodide contents in the iodine aqueous solution is preferably about 1:5 to 1:20, and more preferably about 1:5 to 1:10. The temperature of the dyeing solution is, for example, 20 to 50° C. The immersion time is, for example, 5 seconds to 5 minutes.

[0047] In the crosslinking step, a boron compound is usually used as a crosslinking agent. Examples of the boron compound include boric acid and borax, and boric acid is preferred. The boron compound is usually used in the form of an aqueous solution. In the aqueous solution containing the boron compound, the concentration of the boron compound is, for example, about 0.5 to 15% by weight, and preferably about 1 to 10% by weight. The aqueous solution containing the boron compound may also contain an iodide such as potassium iodide.

[0048] Examples of the crosslinking step include a method of immersing a PVA-based film in an aqueous solution containing a boron compound, a method of applying an aqueous solution containing a boron compound to a PVA-based film, and a method of spraying an aqueous solution containing a boron compound to a PVA-based film. Of these, the method of immersing in an aqueous solution containing a boron compound is preferred.

[0049] In the crosslinking step, the temperature of the aqueous solution containing the boron compound is, for example, 25° C. or higher, preferably about 30 to 85° C., and more preferably about 40 to 70° C. The immersion time is, for example, about 5 to 800 seconds, and preferably about 8 to 500 seconds.

[0050] The washing step is carried out after the crosslinking step as necessary. The washing step is typically carried out by immersing the PVA film in a washing solution. A typical example of the washing solution is pure water. The washing solution may contain an iodide such as potassium iodide. The temperature of the washing solution is, for example, about 5 to 50°C. The immersion time is, for example, about 1 to 300 seconds.

[0051] In addition, when a polarizing film containing the radical scavenger is produced, the radical scavenger may be contained in at least one of the treatment baths in the swelling step, the washing step, the dyeing step, the crosslinking step, and the stretching step. The concentration of the radical scavenger contained in any of the treatment baths cannot be determined in general because it is affected by the number of treatments, treatment time, treatment temperature, etc. of each treatment, but from the viewpoint of efficiently controlling the content of the radical scavenger in the polarizing film, it is usually preferably 0.01% by weight or more, more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, and preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less.

[0052] Furthermore, each treatment bath in the swelling step, the dyeing step, the crosslinking step, the stretching step and the washing step may contain additives such as zinc salts, pH adjusters, pH buffers and other salts. Examples of the zinc salts include zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of the pH adjusters include strong acids such as hydrochloric acid, sulfuric acid and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of the pH buffers include carboxylic acids such as acetic acid, oxalic acid and citric acid and their salts, inorganic weak acids such as phosphoric acid and carbonic acid and their salts. Examples of the other salts include chlorides such as sodium chloride, potassium chloride and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0053] The drying step may be, for example, natural drying, air drying, reduced pressure drying, heat drying, etc., and heat drying is preferred. When heat drying is performed, the heating temperature is, for example, 30 to 100° C. The drying time is, for example, 20 seconds to 10 minutes.

[0054] <Polarizing film> The polarizing film of the present invention comprises the polarizing membrane and a film such as a transparent protective film or an optically functional film laminated to at least one surface of the polarizing membrane.

[0055] The transparent protective film is not particularly limited, and various transparent protective films used in polarizing films can be used. As a material constituting the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. can be used. Examples of the thermoplastic resin include cellulose ester resins such as triacetyl cellulose, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins such as nylon and aromatic polyamide, polyimide resins, polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins) having a cyclo or norbornene structure, polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. In addition, the transparent protective film can be a cured layer formed from a thermosetting resin or an ultraviolet curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone resin. Among these, cellulose ester resins, polycarbonate resins, (meth)acrylic resins, cyclic polyolefin resins, and polyester resins are preferred.

[0056] The thickness of the transparent protective film can be determined as appropriate, but generally, from the viewpoints of workability such as strength and handleability, thinness, etc., it is preferably about 1 to 500 μm, more preferably about 1 to 300 μm, and even more preferably about 5 to 100 μm.

[0057] The transparent protective film may contain any appropriate additive, such as an ultraviolet absorber, an antioxidant, a lubricant, a plasticizer, a release agent, a coloring inhibitor, a flame retardant, an antistatic agent, a pigment, a colorant, etc. In particular, when the transparent protective film contains an ultraviolet absorber, the light resistance of the polarizing film can be improved.

[0058] The optical functional film is not particularly limited, and may be one or more layers of optical functional films that may be used in the formation of liquid crystal displays, such as a reflector, a semi-transmitting plate, a retardation plate (including 1 / 2 or 1 / 4 wavelength plates), a viewing angle compensation film, or a brightness enhancement film such as a linearly polarized light separation film. Examples of polarizing films having the optical functional film include a reflective polarizing film or a semi-transmitting polarizing film obtained by laminating a reflector or a semi-transmitting reflector on the polarizing film, an elliptical polarizing film or a circular polarizing film obtained by laminating a retardation plate on the polarizing film, a wide viewing angle polarizing film obtained by laminating a viewing angle compensation film on the polarizing film, or a polarizing film obtained by laminating a brightness enhancement film on the polarizing film.

[0059] When a film such as the transparent protective film or the optically functional film is attached to both sides of the polarizing film, the films on both sides may be the same or different.

[0060] The surface of the film to which the polarizing film is not attached may be provided with a functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, an anti-glare layer, etc. The functional layer such as the hard coat layer, the anti-reflection layer, the anti-sticking layer, the diffusion layer, the anti-glare layer, etc. may be provided as a part of the film itself, or may be provided as a separate layer from the film.

[0061] The polarizing film and the film, or the polarizing film and the functional layer, are usually attached to each other via a pressure-sensitive adhesive layer or an adhesive layer.

[0062] As the adhesive forming the adhesive layer, various adhesives used in polarizing films can be used, and examples thereof include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinyl porolidone-based adhesives, polyacrylamide-based adhesives, cellulose-based adhesives, etc. Among these, acrylic-based adhesives are preferred.

[0063] Examples of the method for forming the pressure-sensitive adhesive layer include a method in which the pressure-sensitive adhesive is applied to a release-treated separator or the like, dried to form a pressure-sensitive adhesive layer, and then transferred to a polarizing film or the like, or a method in which the pressure-sensitive adhesive is applied to a polarizing film or the like, dried to form a pressure-sensitive adhesive layer, etc. The thickness of the pressure-sensitive adhesive layer is not particularly limited and is, for example, about 1 to 100 μm, and preferably about 2 to 50 μm.

[0064] The adhesive for forming the adhesive layer may be any of various adhesives used in polarizing films, including, for example, isocyanate-based adhesives, polyvinyl alcohol-based adhesives, gelatin-based adhesives, vinyl latex-based adhesives, water-based polyesters, etc. These adhesives are usually used as adhesives made of aqueous solutions (water-based adhesives) and contain 0.5 to 60% by weight of solids.

[0065] The water-based adhesive may contain a crosslinking agent. As the crosslinking agent, a compound having at least two functional groups in one molecule that are reactive with the polymer or other components constituting the adhesive is usually used, and examples of the crosslinking agent include alkylenediamines, isocyanates, epoxies, aldehydes, and amino-formaldehydes such as methylol urea and methylol melamine. The amount of the crosslinking agent in the adhesive is usually about 10 to 60 parts by weight based on 100 parts by weight of the polymer or other components constituting the adhesive.

[0066] In addition to the above, examples of the adhesive include active energy ray curable adhesives such as ultraviolet ray curable adhesives and electron beam curable adhesives. Examples of the active energy ray curable adhesives include (meth)acrylate adhesives. Examples of the curable components in the (meth)acrylate adhesives include compounds having a (meth)acryloyl group and compounds having a vinyl group. Examples of the compounds having a (meth)acryloyl group include alkyl (meth)acrylates such as linear alkyl (meth)acrylates, alicyclic alkyl (meth)acrylates, and polycyclic alkyl (meth)acrylates having 1 to 20 carbon atoms; hydroxyl group-containing (meth)acrylates; and epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate. The (meth)acrylate adhesive may contain nitrogen-containing monomers such as hydroxyethyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, (meth)acrylamide, and (meth)acryloyl morpholine. The (meth)acrylate adhesive may contain polyfunctional monomers such as tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, and EO-modified diglycerin tetraacrylate as a crosslinking component. In addition, compounds having epoxy groups or oxetanyl groups can also be used as cationic polymerization curing adhesives. The compound having an epoxy group is not particularly limited as long as it has at least two epoxy groups in the molecule, and various commonly known curing epoxy compounds can be used.

[0067] The adhesive may contain appropriate additives as necessary, such as coupling agents, such as silane coupling agents and titanium coupling agents, adhesion promoters, such as ethylene oxide, ultraviolet absorbers, deterioration inhibitors, dyes, processing aids, ion trapping agents, antioxidants, tackifiers, fillers, plasticizers, leveling agents, foaming inhibitors, antistatic agents, heat stabilizers, and hydrolysis stabilizers.

[0068] The adhesive may be applied to either the film side (or the functional layer side) or the polarizing film side, or may be applied to both. After lamination, a drying step is performed to form an adhesive layer consisting of a coated and dried layer. After the drying step, ultraviolet rays or electron beams may be irradiated as necessary. The thickness of the adhesive layer is not particularly limited, and when a water-based adhesive or the like is used, it is preferably about 30 to 5000 nm, more preferably about 100 to 1000 nm, and when a UV-curable adhesive, an electron beam-curable adhesive, or the like is used, it is preferably about 0.1 to 100 μm, more preferably about 0.5 to 10 μm.

[0069] The film and the polarizing film, or the polarizing film and the functional layer, may be laminated via an intervening layer such as a surface modification layer, an easy-adhesive layer, a blocking layer, or a refractive index adjustment layer.

[0070] Examples of the surface modification treatment for forming the surface modification layer include corona treatment, plasma treatment, primer treatment, and saponification treatment.

[0071] Examples of the adhesive that forms the easy-adhesion layer include forming materials containing various resins having a polyester skeleton, a polyether skeleton, a polycarbonate skeleton, a polyurethane skeleton, a silicone-based skeleton, a polyamide skeleton, a polyimide skeleton, a polyvinyl alcohol skeleton, etc. The easy-adhesion layer is usually provided on the film in advance, and the easy-adhesion layer side of the film and the polarizing film are laminated with the pressure-sensitive adhesive layer or the adhesive layer.

[0072] The blocking layer is a layer having a function of preventing impurities such as oligomers and ions eluted from the film, etc. from migrating (penetrating) into the polarizing film. The blocking layer may be any layer that is transparent and can prevent impurities from eluting from the film, etc., and examples of materials for forming the blocking layer include urethane prepolymer-based forming materials, cyanoacrylate-based forming materials, and epoxy-based forming materials.

[0073] The refractive index adjusting layer is a layer provided to suppress a decrease in transmittance caused by reflection between layers having different refractive indices such as the film and a polarizing film, etc. Examples of refractive index adjusting materials forming the refractive index adjusting layer include forming agents containing various resins and additives such as silica-based, acrylic-based, acrylic-styrene-based, and melamine-based resins.

[0074] The polarizing film preferably has a polarization degree of 99.98% or more, and more preferably has a polarization degree of 99.99% or more.

[0075] An adhesive layer for bonding other members may be provided on one or both surfaces of the polarizing film. The adhesive layer is preferably a pressure-sensitive adhesive layer. The pressure-sensitive adhesive forming the pressure-sensitive adhesive layer is not particularly limited, and may be appropriately selected and used from, for example, a pressure-sensitive adhesive having an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like as a base polymer. In particular, a pressure-sensitive adhesive having excellent optical transparency, moderate wettability, cohesiveness, and adhesiveness, and excellent weather resistance, heat resistance, etc., such as a pressure-sensitive adhesive containing an acrylic polymer, is preferably used.

[0076] The adhesive layer can be applied to one or both sides of the polarizing film by an appropriate method. For example, the adhesive layer can be applied directly to the polarizing film by preparing an adhesive solution and applying it by an appropriate spreading method such as a casting method or a coating method, or by forming an adhesive layer on a separator and transferring it onto the polarizing film. The thickness of the adhesive layer can be appropriately determined depending on the purpose of use, adhesive strength, etc., and is generally 1 to 500 μm, preferably 5 to 200 μm, and more preferably 10 to 100 μm. The polarizing film having an adhesive layer on at least one side thereof is also called an adhesive layer-attached polarizing film.

[0077] It is preferable that a separator is temporarily attached to cover the exposed surface of the pressure-sensitive adhesive layer for the purpose of preventing contamination, etc., until the pressure-sensitive adhesive layer is put into practical use. This prevents contamination, etc., of the pressure-sensitive adhesive layer under normal handling conditions. As the separator, for example, a suitable thin material such as a plastic film, a rubber sheet, paper, cloth, nonwoven fabric, net, foam sheet, metal foil, or a laminate thereof, which is coated with a suitable release agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide-based, as necessary, is used. EXAMPLES

[0078] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.

[0079] <Example 1> <Preparation of polarizing membrane and polarizing film> As the thermoplastic resin substrate, an isophthalic acid copolymerized polyethylene terephthalate (IPA copolymerized PET) film (thickness: 100 μm) was used. One side of the substrate was subjected to a corona treatment, and an aqueous solution containing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (polymerization degree 1200, acetoacetyl-modification degree 4.6%, saponification degree 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFYMER Z200") in a ratio of 9:1 was applied to the corona-treated surface at 25 ° C. and dried to form a PVA-based resin layer, thereby producing a laminate. The obtained laminate was stretched in the air 4.5 times at 140 ° C. in the direction perpendicular to the longitudinal direction of the laminate using a tenter stretching machine (stretching treatment). Next, the laminate was immersed in a dye bath (aqueous solution with an iodine concentration of 1.0 wt % and a potassium iodide concentration of 7.0 wt %) at a liquid temperature of 25 ° C. for 12 seconds and dyed (dyeing treatment). Next, the laminate was immersed in a crosslinking bath (aqueous solution containing 1.0% by weight of boron, 1.0% by weight of potassium iodide, and 5.0% by weight of a compound represented by the following general formula (9)) at a liquid temperature of 60°C for 21 seconds (crosslinking treatment). Next, the laminate was immersed in a cleaning bath (aqueous solution containing 4.5% by weight of potassium iodide) at a liquid temperature of 25°C for 10 seconds (cleaning treatment). Next, the laminate was dried in an oven at 60°C for 21 seconds (drying treatment) to obtain a laminate having a PVA-based resin layer (polarizing film) with a thickness of 1.2 μm. Next, a linearly polarized light separation film (manufactured by 3M, product name "DBEF") was bonded to the polarizing film side of the obtained laminate having a PVA-based resin layer (polarizing film) via an acrylic adhesive layer with a thickness of 20 μm, and then the thermoplastic resin substrate was peeled off, and an acrylic adhesive layer with a thickness of 20 μm was applied to the peeled surface to produce a polarizing film. The single transmittance was 39.7%. [ka]

[0080] [Method for measuring the iodine content (wt%) in polarizing film] The iodine concentration (wt %) of the polarizing film was determined using an X-ray fluorescence analyzer (manufactured by Rigaku Corporation, product name "ZSX-PRIMUS IV", measurement diameter: ψ20 mm) according to the following formula. Iodine concentration (wt%) = 14.474 x (fluorescent X-ray intensity) / (film thickness) (kcps / μm) Note that the coefficient used to calculate the concentration differs depending on the measuring device, but the coefficient can be obtained using an appropriate calibration curve. The results are shown in Table 1.

[0081] [Evolved gas analysis method] The polarizing film was introduced into a furnace-type pyrolyzer (Frontier Labs, PY-2020iD), and the generated gas was directly introduced into a TOFMS (JEOL, JMS-T100GCV) to perform evolved gas analysis (EGA / TOFMS). The results are shown in Table 1. [Measurement conditions] Temperature rise conditions: 40℃→+10℃ / min→350℃ Interface: Inert fused silica tubing, 2.5m x 0.15mm id Carrier gas: He (1.0 mL / min) Inlet temperature: 300℃ Inlet: Split ratio 20:1 Interface temperature: 300℃ Mass spectrometer: TOFMS Ionization method: EI method Mass range: m / z=18

[0082] [Method for measuring the content (wt%) of radical scavenger in polarizing film] Approximately 20 mg of the polarizing film was collected, weighed, and dissolved by heating in 1 mL of water, then diluted with 4.5 mL of methanol, and the resulting extract was filtered through a membrane filter, and the concentration of the radical scavenger in the filtrate was measured using HPLC (Waters ACQUITY UPLC H-class Bio). The results are shown in Table 1.

[0083] [Evaluation of polarization degree] The degree of polarization of the polarizing film can be measured using a spectrophotometer (manufactured by JASCO, product name "V7100"). As a specific method for measuring the degree of polarization, the parallel transmittance (H0) and crossed transmittance (H90) of the polarizing film are measured, and the degree of polarization can be calculated from the formula: degree of polarization (%) = {(H0-H90) / (H0+H90)}1 / 2 x 100. The parallel transmittance (H0) is the transmittance value of a parallel laminated polarizing film produced by stacking two identical polarizing films so that their absorption axes are parallel to each other. The crossed transmittance (H90) is the transmittance value of a crossed laminated polarizing film produced by stacking two identical polarizing films so that their absorption axes are perpendicular to each other. These transmittances are Y values ​​corrected for luminosity using a 2-degree visual field (C light source) according to JIS Z 8701-1982. The results are shown in Table 1.

[0084] [Evaluation of single-piece transmittance in high temperature environments] The polarizing film obtained above was cut into a size of 5.0 x 4.5 cm so that the absorption axis of the polarizing film was parallel to the long side, and a 1.3 mm alkali-free glass plate was attached to the adhesive layer surface of the polarizing film to prepare a laminate. The obtained laminate was left to stand in a hot air oven at a temperature of 105°C for 96 hours, and the single transmittance (ΔTs) before and after putting it in (heating) was measured. The single transmittance was measured using a spectrophotometer (manufactured by JASCO, product name "V7100") and evaluated according to the following criteria. The measurement wavelength was 380 to 700 nm (every 5 nm). The results are shown in Table 1. ΔTs(%)=Ts 96 -Ts0 Here, Ts0 is the single layer transmittance of the laminate before heating, and Ts 96 is the single layer transmittance of the laminate after heating for 96 hours. The ΔTs(%) is preferably 5≧ΔTs(%)≧0, and more preferably 3≧ΔTs(%)≧0.

[0085] <Example 2> A polarizing film and a polarizing film were prepared in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the crosslinking bath was changed to a crosslinking bath (an aqueous solution containing 1.0% by weight of boron, 1.0% by weight of potassium iodide, and 10.0% by weight of the compound represented by the above general formula (9)). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0086] <Example 3> A polarizing film and a polarizing film were prepared in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the crosslinking bath was changed to a crosslinking bath (an aqueous solution containing 1.0% by weight of boron, 1.0% by weight of potassium iodide, and 10.0% by weight of the compound represented by the above general formula (8)). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0087] <Example 4> A polarizing film and a polarizing film were prepared in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the crosslinking bath was changed to a crosslinking bath (an aqueous solution containing 1.0% by weight of boron, 1.0% by weight of potassium iodide, and 10.0% by weight of the compound represented by the above general formula (7)). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0088] <Example 5> In the above <Preparation of polarizing film and polarizing film>, a laminate was prepared by forming a PVA-based resin layer so that the thickness of the final polarizing film would be 4.8 μm, and a crosslinking bath was changed to a crosslinking bath (an aqueous solution having a boron concentration of 1.0 wt %, a potassium iodide concentration of 1.0 wt %, and a compound represented by the above general formula (9) concentration of 10.0 wt %). A polarizing film and a polarizing film were prepared in the same manner as in Example 1. The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0089] <Example 6> A polarizing film and a polarizing film were produced in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the dyeing bath was changed to a dyeing bath (aqueous solution having an iodine concentration of 0.7% by weight and a potassium iodide concentration of 4.9% by weight) and the crosslinking bath was changed to a crosslinking bath (aqueous solution having a boron concentration of 1.0% by weight, a potassium iodide concentration of 1.0% by weight, and a compound represented by the above general formula (9) of 10.0% by weight). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0090] <Example 7> In the above <Preparation of polarizing film and polarizing film>, a laminate was prepared by forming a PVA-based resin layer so that the thickness of the final polarizing film would be 2.5 μm, and the dyeing bath was changed to a dyeing bath (aqueous solution with an iodine concentration of 0.5 wt% and a potassium iodide concentration of 3.5 wt%), and the crosslinking bath was changed to a crosslinking bath (aqueous solution with a boron concentration of 1.0 wt%, a potassium iodide concentration of 1.0 wt%, and a compound represented by the above general formula (9) of 10.0 wt%). A polarizing film and a polarizing film were prepared in the same manner as in Example 1. The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0091] <Example 8> In the above <Preparation of polarizing film and polarizing film>, a laminate was prepared by forming a PVA-based resin layer so that the thickness of the final polarizing film would be 4.8 μm, and the dyeing bath was changed to a dyeing bath (aqueous solution with an iodine concentration of 0.5 wt% and a potassium iodide concentration of 3.5 wt%), and the crosslinking bath was changed to a crosslinking bath (aqueous solution with a boron concentration of 1.0 wt%, a potassium iodide concentration of 1.0 wt%, and a compound represented by the above general formula (9) of 10.0 wt%). A polarizing film and a polarizing film were prepared in the same manner as in Example 1. The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0092] <Comparative Example 1> A polarizing film and a polarizing film were prepared in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the crosslinking bath was changed to a crosslinking bath (aqueous solution with a boron concentration of 1.0% by weight and a potassium iodide concentration of 1.0% by weight). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0093] <Comparative Example 2> A polarizing film and a polarizing film were produced in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the dyeing bath was changed to a dyeing bath (aqueous solution having an iodine concentration of 0.5% by weight and a potassium iodide concentration of 3.5% by weight) and the crosslinking bath was changed to a crosslinking bath (aqueous solution having a boron concentration of 1.0% by weight, a potassium iodide concentration of 1.0% by weight, and a compound represented by the above general formula (9) of 10.0% by weight). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0094] <Comparative Example 3> In the above <Preparation of polarizing film and polarizing film>, a linearly polarized light separation film (manufactured by 3M, product name "DBEF") was attached to the polarizing film side of the laminate having a PVA-based resin layer (polarizing film) via a 20 μm-thick acrylic adhesive layer, the thermoplastic resin substrate was peeled off, and the peeled surface was coated with a treatment liquid (aqueous solution of 0.5 wt % sodium bicarbonate and 50 wt % isopropyl alcohol: pH 6.0) using a bar coater, dried at 50°C for 60 seconds, and then coated with a 20 μm-thick acrylic adhesive layer to prepare a polarizing film. A polarizing film and a polarizing film were prepared in the same manner as in Example 1. The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0095] <Comparative Example 4> A polarizing film and a polarizing film were produced in the same manner as in Example 1, except that in the above <Preparation of polarizing film and polarizing film>, the dye bath was changed to a dye bath (aqueous solution containing potassium iodide at a concentration of 15.0% by weight and ferric sulfate n-hydrate at a concentration of 2.0% by weight). The results of the above measurements and evaluations of the polarizing film and the polarizing film are shown in Table 1.

[0096] [Table 1]

[0097] In the examples, the polarizing film having an iodine content of more than 10 wt%, a single-unit transmittance of 41% or less, and a peak temperature of the maximum water intensity of 175°C or higher in evolved gas analysis is excellent in the effect of suppressing a decrease in the single-unit transmittance due to coloring of the polarizing film in a high-temperature environment.

[0098] On the other hand, the polarizing film of Comparative Example 1 had a peak temperature of maximum water intensity in evolved gas analysis of 173°C, and therefore had poor effect of suppressing the decrease in single transmittance due to coloring of the polarizing film in a high-temperature environment. The polarizing film of Comparative Example 2 had a single transmittance of 41.5%, and therefore did not meet the standard for single transmittance of the present invention. Furthermore, Comparative Examples 3 and 4 correspond to the polarizing films disclosed in Patent Documents 1 and 2 of the prior art documents, and had a peak temperature of maximum water intensity of less than 175°C in evolved gas analysis, and therefore had poor effect of suppressing the decrease in single transmittance due to coloring of the polarizing film in a high-temperature environment.

Claims

1. A polarizing film formed by adsorbing and orienting iodine on a polyvinyl alcohol film, The iodine content is more than 10% by weight, and the single-piece transmittance is 41% or less; Contains a radical scavenger, a weight ratio of the content of the radical scavenger to the content of the iodine (content of the radical scavenger / content of iodine) is 0.01 or more and 1.0 or less; and A polarizing film characterized in that, in evolved gas analysis, the peak temperature of the maximum intensity of detected water is 175°C or higher under conditions of a heating rate of 10°C / min in the presence of an inert gas and a heating range of 40°C to 350°C.

2. 2. The polarizing film according to claim 1, which has a thickness of 10 μm or less.

3. 3. The polarizing film according to claim 1, wherein the radical scavenger is a compound having a nitroxy radical or a nitroxide group.

4. A polarizing film comprising the polarizing film according to any one of claims 1 to 3 and a transparent protective film or an optically functional film laminated to at least one surface of the polarizing film.

5. 5. The polarizing film according to claim 4, wherein the polarization degree is 99.98% or more.

Citation Information

Patent Citations

  • Method for manufacturing polarizer, polarizer, polarizing plate, optical film, and image display device

    JP2012108202A

  • Game machine

    JP2019180921A

  • Polarizer and polarizing plate

    WO2018186244A1

  • Polarizing film, polarizing plate including said polarizing film, and vehicle on-board image display device including said polarizing plate

    WO2018235461A1

  • Polarizer and polarizing plate

    WO2019103002A1